OPTIMIZATION OF FISH STOCKING DENSITY IN AQUAPONIC SYSTEMS: BALANCING FISH YIELD, PLANT GROWTH, AND ECONOMIC PROFITABILITY ACROSS THREE STOCKING TREATMENTS - Angham Bani Owdeh; Muayad Salman; Medhat Wild Ali; Mohamed Salah Romdhane (Journal of Animal and Plant Sciences, 2025)
This study examines the effects of stocking density on the growth performance of juvenile Nile tilapia (Oreochromis niloticus) and spearmint (Mentha spicata) in a recirculating aquaponic system over a 120-day production cycle. Three stocking densities were tested: 40 fish/m³ (Group G1), 80 fish/m³ (Group G2), and 120 fish/m³ (Group G3). The experiment was conducted at the National Agricultural Research Center (NARC) in Palestine, using 1000-liter units equipped with biofiltration systems and standardized environmental controls. Fish were fed a diet containing 35% crude protein, while mint plants (10 plants per unit) were cultivated simultaneously without additional nutrient supplementation. Data were analyzed using one-way ANOVA followed by Tukey’s HSD post-hoc test (p < 0.05) to assess significant differences in weight gain, survival rates, and plant biomass across treatments. Results indicated that operational costs increased with higher stocking densities, reaching $52.58 for G1, $82.90 for G2, and $113.60 for G3, despite uniform initial setup costs across all groups. Tilapia biomass exhibited a clear density-dependent increase, with final weights of 7.84 kg (G1), 13.49 kg (G2), and 20.22 kg (G3). Correspondingly, net profits rose from $5.68 in G1 to $28.10 in G3. These findings highlight the significance of strategic stocking density management in optimizing the productivity and economic efficiency of aquaponic systems. Implementing cost-effective stocking strategies and refining system design can significantly enhance the viability of aquaponics, particularly for small-scale agricultural operations.
Keywords: Tilapia; Stock Density; Aquaponic; Water Quality